ANALISIS USAHATANI KENTANG DI DESA SINSINGON KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - Alfioni W. Langoy; Eyverson Ruauw; Gene H.M. Kapantow; Celsius Talumingan (COCOS, 2013)
ABSTRACTAlfioni Wandira Langoy. Analysis of Farming Potatoes in Sinsingon Village, East Passi Subdistrict, Bolaang Mongondow Regency, under the guidance of Eyverson Ruauw, as a chairman, Gene H.M. Kapantow, and Celsius Talumingan, as members.The objective of this study is to analyze farming potatoes in Sinsingon Village, East Passi Subdistrict, Bolaang Mongondow Regency. The benefit of this research is a source of information for farmers in order to develop better farming potato. The data used in this study are primary data obtained through direct interviews with farmers techniques based on questionnaire and secondary data obtained from other agencies such as the Sinsingon Village office. The data obtained in this study is analyzed descriptive, and collected data are presented in tabular form and proceed with the calculation of revenues, expenses, income, analysis of (R / C) and breakeven point analysis (BEP).The results showed that the average revenues each hectare potato farm in the Sinsingon Village was Rp.57.503.700, 00. The production process cost of the average each hectare was Rp.21.399.065, 55. So that the average income of farmers per hectare in a single production process was Rp.36.104.634, 45. Potato farm income in the Sinsingon Village Subdistrict, East Passi, Bolaang Bolaang Regency seen from the results of analysis of Return Cost Ratio (R / C) was more than 1, is 2.68 shows that farmers received income in production process was benefit and breakeven point (BEP) were achieved at the level of production of 5836.1 kg and at a price level of Rp.1.405, 06 /kg.